The masses and metallicities of stellar haloes reflect galactic merger histories. Issue 4 (5th December 2017) - D'Souza, Richard; Bell, Eric F
Abstract: There is increasing observational and theoretical evidence for a correlation between the metallicity and the mass of the stellar halo for galaxies with Milky Way-like stellar masses. Using the Illustris cosmological hydrodynamical simulations, we find that this relationship arises because a single massive progenitor contributes the bulk of the mass to the accreted stellar component as well as sets its metallicity. Moreover, in the Illustris simulations, this relationship extends over 3 orders of magnitude in accreted stellar mass for central galaxies. We show that for Milky Way-like mass galaxies, the scatter in accreted metallicity at a fixed accreted stellar mass encodes information about the stellar mass of the dominant accreted progenitor, while the radial density and metallicity gradients of the accreted stellar component encodes information about the time of accretion of the dominant progenitor. We demonstrate that for Milky Way-like mass galaxies, the Illustris simulations predict that the metallicity and the stellar mass of the total accreted stellar component can be reconstructed from aperture measurements of the stellar halo along the minor axis of edge-on disc galaxies. These correlations highlight the potential for observational studies of stellar haloes to quantify our understanding of the most dominant events in the growth history of galaxies. We explore the implications of our model for our understanding of the accretion histories of the Milky Way, M31, and NGC 5128. In particular, a relatively late and massive accretion is favoured for M31; additionally, we provide a first estimate of the accreted stellar mass for NGC 5128.